IMPLEMENTASI ALGORITMA APRIORI DALAM MENENTUKAN POLA PEMBELIAN (CAP N CHRIS CAFÉ & RESTO JEPARA) BERBASIS WEB - Misbakhus Surur; Heru Saputro; Noor Azizah (Journal of Information System and Computer, 2022)
With the rapid advancement of technology at this time, there are many sales transactions received every day. The increase in sales certainly brings good. However, with the existence of sales activities, the sales data for the food menu is getting more and more. And the data only serves as an archive only.This study aims to create a website-based application with the Apriori Algorithm by utilizing sales transaction data, by determining the relationship between items from sales data, in this case the food or beverage ordered so that consumer purchasing patterns can be found. The results of research conducted from data from 16 transactions obtained 4 association rules with a minimum support of 3 and a minimum confidence of 60.